Perancangan Produk Fashion Kontemporer Berdasarkan Budaya Peranakan Dengan Menerapkan Motif Batik Pesisir - Enrico Enrico (JURNAL RUPA, 2023)
Fashion industry in Indonesia has been growing tremendously by adapting the archipelago's culture as its unique identity. Peranakan as a result of acculturation of local culture with that of China and Dutch which is infused with myriads of aesthetic values. This design is a representation of cultural transformation that still holds the Peranakan identity while looking to fit into the target market as well as the current trend. This is done by way of qualitative approach by accumulating primary data through observation, experiment and also secondary data via literature study. FRANGIPANI design method has 6 stages from searching for inspiration to realizing the product and trialing it to the public. The purpose of this research is to introduce, promote and preserve the Peranakan culture as a fashion product that can be accepted by the current market. We hope this research will be one of the solutions for the Indonesian fashion industry and players to further develop products with Indonesian culture.